Comparison of Urine and Plasma Peptidome Indicates Selectivity in Renal Peptide Handling. Issue 5 (23rd April 2018) - Magalhães, Pedro; Pontillo, Claudia; Pejchinovski, Martin; Siwy, Justyna; Krochmal, Magdalena; Makridakis, Manousos; Carrick, Emma; Klein, Julie; Mullen, William; Jankowski, Joachim; Vlahou, Antonia; Mischak, Harald; et al.
Abstract : Purpose: Urine is considered to be produced predominantly as a result of plasma filtration in the kidney. However, the origin of the native peptides present in urine has never been investigated in detail. Therefore, the authors aimed to obtain a first insight into the origin of urinary peptides based on a side‐by‐side comprehensive analysis of the plasma and urine peptidome. Methods: Twenty‐two matched urine and plasma samples are analyzed for their peptidome using capillary electrophoresis coupled to mass spectrometry (CE‐MS; for relative quantification) and CE or LC coupled to tandem mass spectrometry (CE‐ or LC‐MS/MS; for peptide identification). The overlap and association of abundance of the different peptides present in these two body fluids are evaluated. Results: The authors are able to identify 561 plasma and 1461 urinary endogenous peptides. Only 90 peptides are detectable in both urine and plasma. No significant correlation is found when comparing the abundance of these common peptides, with the exception of collagen fragments. This observation is also supported when comparing published peptidome data from both plasma and urine. Conclusions and clinical relevance: Most of the plasma peptides are not detectable in urine, possibly due to tubular reabsorption. The majority of urinary peptides may in fact originate in the kidney. The notable exception is collagen fragments, which indicates potential selective exclusion of these peptides from tubular reabsorption. Experimental verification of this hypothesis is warranted.